Torture in respect to imprisonment: A Croatian perspective - Gašparić, Asea (Central European Academy Law Review, 2023)
The discussion of strengthening prisoners’ rights is rooted in human rights principles and the recognition of inherent dignity. Historically, torture was widely accepted, but enlightenment ideals led to its condemnation. International efforts and universal legal documents shaped global attitudes towards the prohibition of torture. This comprehensive analysis explores the safeguarding of individuals deprived of liberty, primarily from an international perspective, with a focus on the European Convention on Human Rights and its pivotal Article 3, which explicitly prohibits torture and inhumane or degrading treatment. The examination encompasses material and procedural obligations imposed on states, providing a nuanced understanding of the fundamental rights tied to human dignity and physical integrity. Significantly, the study delves into the jurisprudence of the European Court of Human Rights, emphasising cases involving Croatia and revealing persistent shortcomings in prison conditions.